THE EFFECTIVENESS OF THE COMBINATION OF DEMONSTRATION AND ROLE-PLAY METHODS TO IMPROVE KNOWLEDGE ABOUT CHOKING MANAGEMENT - Alhidayat, Nurun Salaman; Latif, Aulia Insani (Journal of Islamic Nursing, 2022)
The child mortality rate increases yearly, and 57 are due to a lack of understanding of the general public about first aid for choking patients. This study aims to determine the effectiveness of the combined demonstration and roleplay method in increasing knowledge about choking management in junior high school students. This study used a quasi-experimental research design with a non-equivalent control group design. The sampling technique used purposive sampling with a sample of 60 junior high school children, consisting of 30 intervention and 30 control groups. The results showed that the Demonstration and Role Play methods effectively increased choking management in junior high school students with a p-value of 0.001. Meanwhile, the control group who was given education with leaflets showed a p-value of 0.004 which means there was also a significant effect after the action was presented. This study shows that providing health education through a combination of demonstration and roleplay methods is proven more effective in increasing knowledge about choking management in junior high school students than the standard method through leaflets. Keywords: Chocking, Demonstration, Role Play, Knowledge, Junior High School Students